Relationship of Mother Characteristics, Knowledge, Husband Support with Participation in Pregnant Women Classes - NK, Ayu Sugiartini; NM, Ari Febriyanti (Jurnal Kebidanan, 2023)
Pregnant Mother Class is a means to learn together about health for pregnant women, in the form of face-to-face groups which aims to increase the knowledge and skills of mothers regarding pregnancy, pregnancy care, childbirth, postnatal care, care for newborns, myths, infectious diseases. and birth certificates. This study aims to determine the participation of pregnant women in the class of pregnant women and the factors that influence it. This was a cross-sectional study conducted in the Catchment Area of Primary Health Center (PHC) Denpasar. A sample of 50 trimester III pregnant women, either primiparous or multiparous, who came and participated in the class of pregnant women mothers was obtained through multistage sampling. Data were gained via interviews using a structured questionnaire. Determinants were analyzed using chi-square.  The results of the research found that most of them (68%) actively participated in the class of pregnant women. The results of bivariate analysis showed that there is a significant relationship between parity (p=0.03), knowledge (p=0.00), husband's support (p=0.01), with the participation of mothers in pregnant women classes.Kelas Ibu Hamil merupakan sarana untuk belajar bersama tentang kesehatan bagi ibu hamil, dalam bentuk tatap muka dalam kelompok yang bertujuan untuk meningkatkan pengetahuan dan keterampilan ibu-ibu mengenai kehamilan, perawatan kehamilan, persalinan, perawatan nifas, perawatan bayi baru lahir, mitos, penyakit menular dan akta kelahiran. Tujuan penelitian ini adalah mengetahui keikutsertaan ibu hamil mengikuti kelas ibu hamil dan faktor yang mempengaruhinya. Desain penelitian ini adalah cross-sectional analitik. Subjek penelitian menggunakan 50 ibu hamil trimester III baik primipara atau multipara yang datang dan ikut serta kelas ibu hamil di wilayah Puskesmas Kota Denpasar dengan analisis yang digunakan adalah chi-square. Hasil penelitian didapatkan sebagian besar (68,0%) responden aktif mengikuti kelas ibu hamil. Hasil bivariat menunjukkan terdapat hubungan yang signifikan antara paritas (p= 0,03), pengetahuan (p= 0,00), dukungan suami (p= 0,01) dengan keikutsertaan ibu mengikuti kelas ibu hamil.